Child mental health in Sierra Leone: a survey and exploratory qualitative study. Issue 1 (December 2016) - Yoder, Hélène; Tol, Wietse; Reis, Ria; Jong, Joop
Abstract Background This study complements the growing amount of research on the psychosocial impact of war on children in Sierra Leone by examining local perceptions of child mental health, formal and informal care systems, help-seeking behaviour and stigma. Methods The study combined: (1) a nationwide survey of mental health care providers, with (2) exploratory qualitative research among service users and providers and other stakeholders concerned with child and adolescent mental health, with a particular emphasis on local explanations and stigma. Results Formal mental health care services are extremely limited resulting in an estimated treatment gap of over 99.8 %. Local explanations of child mental health problems in Sierra Leone are commonly spiritual or supernatural in nature, and associated with help-seeking from traditional healers or religious institutions. There is a considerable amount of stigma related to mental disorders, which affects children, their caregivers and service providers, and may lead to discrimination and abuse. Conclusions Child and Adolescent Mental Health (CAMH) care development in Sierra Leone should cater to the long-term structural effects of war-violence and an Ebola epidemic. Priorities for development include: (1) the strengthening of legal structures and the development of relevant policies that strengthen the health system and specifically include children and adolescents, (2) a clearer local distinction between children with psychiatric, neurological, developmental or psychosocial problems and subsequent channelling into appropriate services (3) supplementary CAMH training for a range of professionals working with children across various sectors, (4) specialist training in CAMH, (5) integration of CAMH care into primary health care, education and the social welfare system, (6) further research on local explanations of child mental disorders and the effect they have on the well-being of the child, and (7) a careful consideration of the role of religious healers as care providers.